2017
DOI: 10.3389/fpsyg.2017.00931
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Features Influence Musical Choices Across Multiple Genres

Abstract: Based on a large behavioral dataset of music downloads, two analyses investigate whether the acoustic features of listeners' preferred musical genres influence their choice of tracks within non-preferred, secondary musical styles. Analysis 1 identifies feature distributions for pairs of genre-defined subgroups that are distinct. Using correlation analysis, these distributions are used to test the degree of similarity between subgroups' main genres and the other music within their download collections. Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…), the musical is able to connect with audiences that may be less familiar with hip-hop or rap (Kajikawa, 2018). Music researchers have also established that audiences are much more likely to engage with music that shares the acoustic features of their preferred main genre (Barone et al, 2017). Further, different cultures and languages create unique communication structures, patterns and rhythms which often directly influence what is known as the prosodic patterns of speech that are then directly reflected in music from these cultural groups (Barone et al, 2017).…”
Section: Redefining Mainstream Culturementioning
confidence: 99%
“…), the musical is able to connect with audiences that may be less familiar with hip-hop or rap (Kajikawa, 2018). Music researchers have also established that audiences are much more likely to engage with music that shares the acoustic features of their preferred main genre (Barone et al, 2017). Further, different cultures and languages create unique communication structures, patterns and rhythms which often directly influence what is known as the prosodic patterns of speech that are then directly reflected in music from these cultural groups (Barone et al, 2017).…”
Section: Redefining Mainstream Culturementioning
confidence: 99%
“…Another strand of research on modeling users' music preferences leverages content features, e.g., acoustic features. It has been shown that the distribution of acoustic features of a user's preferred genre substantially influences the user's choice of music within other genres [28]. Also, acoustic features have been utilized to model users' preferences under different contextual conditions, in order to refine recommendation quality [29].…”
Section: Related Workmentioning
confidence: 99%
“…Various metadata about users are also housed in the database, including user ID, total number of downloads and user country. Because of its size and the nature of the data it contains, the database is an excellent tool for cultural and social investigations relating to music [23][24][25][26].…”
Section: Description Of the Datamentioning
confidence: 99%